Giant Cell Tumor of the Right Distal Radius Campanacci Iii Treated with Wide Excision and Space Filler Using Prefabricated Polymethyl Methacrylate (Pmma) Bone Cement: A Case Report - Magetsari R (Journal of Global Pharma Technology, 2019)
ABSTRACT Background: Giant cell tumor of bone (GCT) is the most common benign aggressive primary bone tumor (metastatic rate less than 5% of cases). The hallmark appearance of GCT is an expansile lesion which is centrally radiolucent with formation of a thin neocortex at the border of the lesion (epiphysis and metaphysis). Campanacci grade is the classification system for giant cell tumors. Grade I tumors are confined within the cortex, grade II expand to cortex, and grade III perforating cortex with higher incidence of recurrence and transformation into malignancy. Functional outcome of the wrist joint was evaluated using Mayo wrist score (pain intensity, functional status, range of movement, and grip strength).Case Report: A 39 years old male presented lump in his right wrist joint since 6 months ago. The patient complained of decreasing range of motions and palpable mass that increase progressively over time. Slight pain was also felt around the wrist joint. He sought traditional (masseuse) therapy for the last 6 months, but the complaint persisted. He then underwent operation (tumor excision and augmented graft) in our institution. The graft was made from PMMA bone cement and designed identically similar to distal part of the patient’s radius. Histopathologic analysis was consistent with Giant cell tumor. We evaluated patient’s functional outcome using Mayo wrist score, with satisfactory result.Discussion : Most common method of replacing distal part of radius after excision of GCT was grafting using proximal fibula or ceramic prosthesis. There has never been a published clinical trial of using PMMA as a space filler. Nonetheless we used prefabricated PMMA bone cement based graft to mimic the bone in order to prevent the risk of recurrence and to achieve good functional outcome. We took the measurement of the patient’s left radius using X-ray as a model, then fabricate the PMMA bone cement in the Anatomy laboratory according to the model’s measurement. Although it’s not a popular method, but after 6 months of follow up satisfactory functional outcome was achieved (Mayo wrist score) and without sign of recurrence or metastatic.Conclusion: After excision of the GCT, prefabricated PMMA bone cement could be considered as one alternative of space-filling material to achieve good functional outcome.Keywords : Giant cell tumor, Radius, Excision, Bone Cement, Polymethyl Methacrylate, Graft